Changes in the menstrual hygiene management facilities and usage among Bangladeshi school girls and its effect on school absenteeism from 2014 to 2018 - Farjana Jahan; Noshin Sayiara Shuchi; Abul Kasham Shoab; Mahbub-Ul Alam; Sk. Md. Kamrul Bashar; Khairul Islam; Hasin Jahan; Mahadi Hasan; Md. Masud Alam; Mahbubur Rahman (Taylor & Francis Group, 2024)
Background The lack of menstrual hygiene management (MHM) information and facilities in schools is a major contributor to adolescent girls' school absenteeism in low- and middle-income countries like Bangladesh. Objectives This paper examines the changes over time in school MHM facilities, knowledge and perceptions among adolescent girls, in relation to school absenteeism between 2014 and 2018 in Bangladesh. Methods We examined changes in MHM and school absenteeism among schoolgirls using nationally representative data from the Bangladesh National Hygiene Baseline Survey 2014 and National Hygiene Survey 2018. Given the repetitive nature of our data and its clustering within participants, our method included performing descriptive analysis, bivariate analysis, and multivariate Generalised Estimating Equation (GEE) modelling to analyse these changes. Results Results showed that adolescent girls' menstruation-related absenteeism decreased between 2014 and 2018. Percentage of adolescents who missed school decreased from 25% to 14% (PD: −11; CI: −16 to −6.1), while the average number of missed days reduced from 2.8 to 2.5 (PD: −0.33; CI: −0.57 to −0.10). In the GEE model, we found that living in rural areas (coef: −5.6; CI: −10.06 to −1.14), parental restrictions on going outside (coef: 4.47; CI: 0.75 to 8.2), education levels of girls (coef: −9.48; CI: −14.17 to −4.79), girl's belief that menstruation affects school performance (coef: 23.32; CI: 19.71 to 26.93), and using old cloths (coef: −4.2; CI: −7.6 to −0.79) were significantly associated with higher absenteeism. However, participant's age, type of school, knowledge of menstruation before menarche, receiving information regarding MHM, separate place for changing absorbents, and separate latrine and urine facility were not significantly associated with the changes in absenteeism over time. Conclusion This paper emphasised the associations between changes in school absenteeism, parental restrictions on students, students' education levels, and menstruation-related misperceptions. Ongoing research, policy reviews, and targeted interventions to improve MHM perceptions among girls are required to provide long-term benefits for adolescent girls in Bangladesh.